Identification of Ectoparasites in Cats (Felis domestica) in Mandau District, Duri City, Riau - Windi Olivia Ningsih; Radith Mahatma (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Felis domestica (cat) is an animal that is much liked and kept because of its characteristic shapeunique body, eye, and coat color. With these advantages become powerspecial attraction for cats to be maintained. This study aims to determine the types of ectoparasites in cats and determine the prevalence and intensity of attacks ectoparasites found in the District Mandau, City of Duri, Riau. This research was conducted in December 2022 – February 2023. Sampling was carried out descriptively referring to book references, and analysed using the prevalence and intensity formulas. The results show is three types of ectoparasites namely Felicola subrostratus, Ctenocephalides felis, and Ixodes ricanus. The calculation results show highest prevalence of ectoparasites in species F. subrostratus (32,5%), while lowest prevalence show in species I. ricinus (2,5%). The highest intensity of ectoparasites show in species F. subrostratus (5,7), while lowest intensity show in species I. ricinus (1,5). Prevalence of total ectoparasites in study included into the very frequently infected category and the total intensity belongs in medium category.